Importance of Flexibility of Employment in a Professional Education of Persons Endangered by a Social Exclusion - Dobrowolska, Malgorzata (European Journal of Economics and Business Studies, 2016)
The paper includes description of selected results of the Author's research carried out in the last 10 years (2005 - 2015) focused on flexibility of employment. The most important notions related to flexible forms of employment have been indicated. At the end of the paper the author presents results of the research on a group of n = 489 persons endangered by a social exclusion, professional career of which were monitored after conclusion of programmes co-financed by the resources of the European Social Fund. Education of persons from groups endangered by a social exclusion is decisive for effective social-and-professional functioning, adequately to changing labour market and changes in economics.
Keywords: flexible forms of employment, professional problems of persons endangered by social exclusion.